Development of High Entropy Alloy (HEA) as catalyst for Azo dye degradation in Fenton process - Abu Hassan, Nur Hudawiyah; Mat Natsir, Nisa Syukrina; Ab Rahman, Siti Noramira; Mohd Daud, Farah Diana; Jamal, Nur Ayuni Jamal; Ibrahim, Nor Fadhilah; Nordin, Norhuda Hidayah (IOP Publishing Ltd, 2021)
Azo dye is widely used in the textile industry since it is cost effective and simple to use . However, it becomes a continuous source of environmental pollution due to its carcinogenicity and toxicity. Various methods had been used to remove the azo dye in solution. One of the famous and repeatedly used is Fenton process. The Fenton’s process is one of the advanced oxidation process where iron catalysed hydrogen peroxide to generate hydroxyl radical. Treating azo dyes in solution requires a catalyst to enhance the process of degradation. Herein, high entropy alloy (HEA) has been proposed as a catalytic material to enhance the performance of Fenton process for azo dye degradation. HEA has been reported as a promising catalyst due to its high surface area. The higher the number of active sites, the higher the rate of azo dye degradation as more active sites are available for adsorption of azo dyes. The results have shown that HEA can be used as a catalyst to fasten the Fenton’s reaction since the degradation time is proven to be shorter in the presence of HEA. The method derived from the result of this study will contribute in treating azo dyes for wastewater management in Fenton process.